The Effect of Innovation & Ability on Competitive Advantage Mediated by Creativity Brand Ice Cream & Tea XYZ in Cikarang. - Dio Nudia Fallah; Galih Khoirul Ichwan; M. Malik Yassin Supriyadi; Retno Purwani Setyaningrum (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study analyzes the effect of innovation and ability on competitive advantage, mediated by creativity, at Brand Ice Cream & Tea XYZ in Cikarang. XYZ is a fictitious name used to maintain the confidentiality of the real business studied in this research. Using a quantitative approach, data were collected through a Likert-scale questionnaire with 74 respondents selected purposively. The results show that innovation significantly affects competitive advantage, both directly and through creativity as a mediating variable. However, ability only affects creativity and does not have a direct impact on competitive advantage. The survey also revealed significant dissatisfaction among respondents regarding the impact of innovation and ability on the competitive position of Brand Ice Cream & Tea XYZ in Cikarang. This indicates the need for improvements in innovation, ability, and product differentiation to strengthen market position and competitiveness amidst the growing number of competitors. This study contributes to understanding the dynamics of competitive advantage in the food and beverage industry.